Dukungan Sosial, Self-Efficacy dan Resiliensi pada Perawat yang Menjaga Pasien Covid-19 - Lintang Tejaratri (Dinasti Research, 2024)
Changes in the Covid-19 pandemic situation require resilience to deal with it, especially for healthcare workers, including nurses. This study aims to examine the effect of social support and self-efficacy on resilience in nurses who care for Covid-19 patients. This study uses a questionnaire, in the form of resilience scale, social support scale, and self-efficacy scale. This study involved 50 nurses working in the Covid-19 referral hospital with characteristics that took care of Covid-19 positive patients directly. The sampling technique used was purposive sampling. Analysis of the data used in this study is multiple regression analysis. The result of this study showed resilience among nurses was significantly affected by social support and self-efficacy.